THE CORRELATION HUSBAND SUPPORT WITH READINESS TO FACE LABOR IN PREGNANT MOTHERS TRIMESTER III AT PARAMITRA MEDIKA 1 CLINIC BEKASI TAHUN 2021 - Friska Junita; Yuliana , Hanita Indra (Jurnal Medicare, 2022)
Pregnancy is an important event that demands the role of all family member, support during pregnancy is needed for pregnant women, especially from the closest people. Support and role from husband during pregnancy and childbirth has been shown to increase the readiness of pregnant women to face pregnancy and childbirth. Research Purpose : To determine the relationship between husband and readiness to face childbirth in third trimester pregnant women at Paramitra Medika 1 Clinic. Research Methods : This research was conducted at Paramitra Medika 1 Clinic on June 28 to July 30, 2021. This research uses an observational analytic design with a cross sectional approach. The number of sample used was 50 respondents using a questionnaire measuring instrument. This research uses univariate and bivariate analysis using statistical tests. Result : Most of husband’s support with readiness on facing childbirth in third trimester pregnant women in the sufficient category as many as 24 people (48%), the good category as many as 22 people (44%), and the less category as many as 4 people (8%). Conclusion : There is no significant relationship between husband’s support and readiness to face childbirth in third trimester pregnant women, P=0,442.